2015
DOI: 10.3389/fmicb.2015.00701
|View full text |Cite
|
Sign up to set email alerts
|

Legacy effects of anaerobic soil disinfestation on soil bacterial community composition and production of pathogen-suppressing volatiles

Abstract: There is increasing evidence that microbial volatiles (VOCs) play an important role in natural suppression of soil-borne diseases, but little is known on the factors that influence production of suppressing VOCs. In the current study we examined whether a stress-induced change in soil microbial community composition would affect the production by soils of VOCs suppressing the plant-pathogenic oomycete Pythium. Using pyrosequencing of 16S ribosomal gene fragments we compared the composition of bacterial communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 57 publications
1
48
1
1
Order By: Relevance
“…This suggests that these compounds might contribute to the ‘disease suppressiveness’ of soils (low disease incidence occurring despite the presence of a virulent pathogen), although this property has been traditionally linked to nonvolatile bacterial metabolites such as 2,4‐diacetylphloroglucinol (Weller et al , ). Indeed, a recent study revealed that changes in soil bacterial community composition caused by anaerobic disinfestation coincided with a loss of emission of Pythium suppressing volatiles and with an increase of hyacinth root infection by the same pathogen (van Agtmaal et al , ).…”
Section: Indirect Effects Of Bacterial Volatiles On Plant Health: Affmentioning
confidence: 99%
“…This suggests that these compounds might contribute to the ‘disease suppressiveness’ of soils (low disease incidence occurring despite the presence of a virulent pathogen), although this property has been traditionally linked to nonvolatile bacterial metabolites such as 2,4‐diacetylphloroglucinol (Weller et al , ). Indeed, a recent study revealed that changes in soil bacterial community composition caused by anaerobic disinfestation coincided with a loss of emission of Pythium suppressing volatiles and with an increase of hyacinth root infection by the same pathogen (van Agtmaal et al , ).…”
Section: Indirect Effects Of Bacterial Volatiles On Plant Health: Affmentioning
confidence: 99%
“…The relationship between community composition and VOCs production is in accordance with previous studies (Garbeva et al 2014a;Hol et al 2015;Tyc et al 2015;Van Agtmaal et al 2015;El Ariebi et al 2016). In this regard, the presence of low-abundant species in the microbial community, such as observed for the Paenibacillus strain in Chapter 3, can significantly contribute to the emission of certain VOCs such as pyrazines with antifungal activity .…”
Section: Factors Influencing the Composition And Biological Activity supporting
confidence: 89%
“…Many studies have shown that bacterial volatiles play a major role in the suppression of soil-borne fungi (Zou et al, 2007;Garbeva et al, 2011a;van Agtmaal et al, 2015). In chapter four I also detected strong anti-fungal and anti-oomycetal activity caused by the volatile blends produced by the four tested bacteria cultivated in monocultures or mixed cultures.…”
Section: Influence Of Bacterial Volatiles On Fungal and Oomycetal Orgmentioning
confidence: 77%
“…The high amount of dimethyl di-and trisulfide detected in both monocultures and interactions indicate that these compounds are commonly produced. Many studies have shown that bacterial volatiles play a major role in soil fungistasis (Zou et al, 2007;Garbeva et al, 2011a;Garbeva et al, 2014b;van Agtmaal et al, 2015).…”
Section: Discussionmentioning
confidence: 99%